KONSTRUKSI MASYARAKAT TENTANG STUNTING DI KECAMATAN SUMBERASIH KABUPATEN PROBOLINGGO - Hidayah, Delia Intan (Paradigma, 2022)
Abstract Data from the 2013 Basic Health Research recorded that there were still many Indonesian children under five with health cases and experiencing malnutrition as much as 40% of the total number of children under five in Indonesia. Stunting is a problem that is currently the most intensively being prevented. This is because the number of stunting toddlers in each area is very high, especially in Sumberasih District, Probolinggo Regency. The growth of stunted toddlers will experience a slowdown in height and weight. Unbalanced height with body weight will be seen when measured and compared with standard sizes according to the health office. This condition occurs from various factors, most of which are caused by a lack of nutrition and protein intake during the growth period or while in the mother’s womb. The family as the first unit that is a place for education and fulfillment of children’s needs has an important role in supervising and overseeing every stage of child development. It is based on this problem that the researcher wants to examine how the community constructs stunting in Sumberasih District, Probolinggo Regency. This study uses a qualitative method with a grounded theory approach. The concept of Peter L. Berger and Luckmann’s thinking and the concept of social construction is used to analyze research data. From the results of the combination of theory and methodology, the results of the study show that the people in the two research location villages, namely Sumberbendo Village and Banjarsari Village, have different constructions. Community Construction regarding stunting in Sumberasih District can be seen through three processes, namely externalization, objectivation, and internalization which process dialectically. The Banjarsari Village community constructs stunting toddlers similar to cases of malnutrition. Whereas in Sumberbendo Village it was stated that the problem of stunting toddlers was more to the causal factor, namely the heredity of their parents. In addition, there are also objective and subjective realities built by the community and medical personnel. Keywords: Toddler Stunting, Community, Reality, Social Construction, Knowledge